2004
DOI: 10.1038/sj.cr.7290234
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Granulosa cells during follicular atresia: relationship with steroids and insulin-like growth factors

Abstract: It is well known that during mammalian ovarian follicular development, the majority of follicles undergo atresia at various stages of their development. However, the mechanisms controlling this selection process remain unknown. In this study, we investigated apoptosis in granulosa cells during goat follicular atresia by terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL). The changes in the levels of steroids, insulin-like growth factors (IGFs) and IGF receptors were studied by radioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(95 citation statements)
references
References 31 publications
3
90
1
1
Order By: Relevance
“…This indicates that the WID system we have developed can best mimic group culture in efficiency, while allows identification of oocyte origin. Our previous studies have shown that GCs apoptosis is an underlying mechanism of follicular atresia in the goat (Yu et al 2003(Yu et al , 2004 as in other animals (Liu et al 2003). Most of the studies on the effect of GCs apoptosis on oocyte developmental competence have so far been conducted in the bovine and using group culture systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the WID system we have developed can best mimic group culture in efficiency, while allows identification of oocyte origin. Our previous studies have shown that GCs apoptosis is an underlying mechanism of follicular atresia in the goat (Yu et al 2003(Yu et al , 2004 as in other animals (Liu et al 2003). Most of the studies on the effect of GCs apoptosis on oocyte developmental competence have so far been conducted in the bovine and using group culture systems.…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized that apoptotic cell death is an underlying mechanism of cell loss during follicular atresia (Tilly et al 1991, Hsueh et al 1994, Liu et al 2003, Yu et al 2003, 2004. While the detection of granulosa cells (GCs) apoptosis has been widely used to identify atretic follicles, very little evidence for its use as a marker of oocyte quality exists.…”
Section: Introductionmentioning
confidence: 99%
“…This is possibly due to an insufficient response to nutrition by the CL to secrete progesterone or insufficient energy to influence progesterone secretion during the luteal phase of the estrous cycle. The level of progesterone was not significantly different among atretic, slightly atretic, and healthy follicles (Yu et al 2004), but testosterone elevated at all stages of follicular growth in the later stages of follicular atresia (Moor et al 1978, Carson et al 1981. The follicular fluid testosterone concentration was decreased in follicles O2.5 mm except in R group ewes (Fig.…”
Section: Parametersmentioning
confidence: 99%
“…Suggested mechanisms of ovarian insufficiency rely on either a decreased oocyte pool [12], augmented follicular atresia [51,112] and/or altered folliculogenesis [78]. The clinical presentation of ovarian insufficiency varies significantly.…”
Section: Fmr1 Gene Mutations and Reproductive Agingmentioning
confidence: 99%